Idiopathic Intracranial Hypertension - J Gordon Millichap (Pediatric Neurology Briefs)
Sex distribution and frequency of obesity in children with idiopathic intracranial hypertension were evaluated at Meyer Children Hospital, Rappaport School of Medicine, Haifa, and other centers in Israel.